2011
DOI: 10.1186/1472-6963-11-144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of interdisciplinarity in cancer care

Abstract: BackgroundTeamwork is a key component of the health care renewal strategy emphasized in Quebec, elsewhere in Canada and in other countries to enhance the quality of oncology services. While this innovation would appear beneficial in theory, empirical evidences of its impact are limited. Current efforts in Quebec to encourage the development of local interdisciplinary teams in all hospitals offer a unique opportunity to assess the anticipated benefits. These teams working in hospital outpatient clinics are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 57 publications
0
33
0
5
Order By: Relevance
“…4 Teamwork is especially important for patients with cancer, who commonly receive complex and potentially toxic treatments involving many different care professionals. Although research has characterized teamwork for patients with cancer in outpatient settings, 7,8 little is known about the quality of teamwork and collaboration between nurses and physicians of various types caring for patients in adult inpatient oncology units. We aimed to characterize teamwork among professionals in the inpatient oncology setting and to determine what barriers exist to establishing strong collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…4 Teamwork is especially important for patients with cancer, who commonly receive complex and potentially toxic treatments involving many different care professionals. Although research has characterized teamwork for patients with cancer in outpatient settings, 7,8 little is known about the quality of teamwork and collaboration between nurses and physicians of various types caring for patients in adult inpatient oncology units. We aimed to characterize teamwork among professionals in the inpatient oncology setting and to determine what barriers exist to establishing strong collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more medical societies and institutions have come to accept the importance of using a multidisciplinary approach in cancer care to provide patients with optimal treatment for their specific characteristics 1720. In this audit, we found that 35% of patients at the ICO were not presented to the board.…”
Section: Discussionmentioning
confidence: 92%
“…For Freidson (1970), this device of professional self-regulation has not yet attained its optimal development, peers often opting for an avoidance strategy rather than a real sanction. Communication between healthcare professionals (O'neill & Twelves, 2002), and cross-cutting approaches (Tremblay et al, 2011) are necessary in the face of such treatments.…”
Section: Discussionmentioning
confidence: 99%